Analysis of Metacognitive Ability Analysis Based on Information Processing Theory Material Linear Equations and Linear Inequalities in one Variable in Students With Field Dependent and Field Independent Learning Styles - rosita, rosita; Huda, Nizlel; Siburian, Jodion (International Journal Labs, 2025)
In learning activities, of course students cannot be separated from mathematical problems which are focused on efforts to train students' thinking patterns in using their thinking potential. Apart from that, learning Mathematics aims to equip students with solving skills problem, Literacy Numeracy, logical, reasoning, abstract, systematic and creative. Facts in the field, researchers found problems with students' metacognitive abilities in Field Dependent and Field Independent learning styles based on information processing theory. This research is a type of qualitative research that uses descriptive research methodology. These subjects were selected using purposive sampling (purposeful sampling). This research was conducted at SMP-IT Ash-Shidiqi Batanghari in the odd semester 2022/2023. The subjects were 4 research subjects. The instrument used in this research was the GEFT (Group Embedded Figures Test) to find students' learning styles including the filed category dependent or filed independent, after that students are given a test question sheet. Then, based on the question sheet, the researcher conducted interviews to research subjects. The data obtained were analyzed using steps (1) transcribe data obtained from think aloud and interviews, (2) reduce data, (3) coding data, and (4) describing information processing on students' metacognitive abilities in linear equations and inequalities material linear one variable. Based on the results of the research and analysis that has been carried out, it can be concluded that students' metacognition in solving problems consists of four indicators, namely Tacit use (use of thinking without awareness), Aware use (use of thinking with awareness), Strategic use (use of strategic thinking) Reflective use (use reflective thinking).